Clínica Médica e Cirúrgica de Pequenos Animais. - Santos, Shammara Noleto (Universidade Federal do Tocantins, 2023)
The Urinary Tract Disease Lower Felines (FLUTD) is a very common disease in domestic cats. The diagnosis is made by ruling out other causes. Some animals may have relapses. The patient's condition can be characterized by hematuria, dysuria, pollakiuria, strangury, with or without urethral obstruction (OSBORNE et al., 1996). The disease has been compared to human interstitial cystitis due to the findings of cystoscopy are similar, so the cat has been considered the animal model for this disease in humans, such as edema of the bladder mucosa, and petechiae in the lamina propria (Westropp; TONY BUFFINGTON 2004; BUFFINGTON, 2011; Lemberger et al, 2011).. This report is described and discussed a case of FLUTD, covering discussions about the diagnosis. The clinical case was accompanied during supervised mandatory, held at the World Veterinary Clinic Animal Farm in Araguaina-TO, from October 19, 2015 through December 22th 2015.